An MCM-based microsystem for colorimetric detection of biomolecules in biological fluids - Minas, Graça (2006)
This paper presents a multichip module microsystem for biological fluid analysis. It is composed of three parts, namely 1) CMOS silicon optical detection microsystem, which includes a photodetector and a light-to-frequency converter for readout; 2) dielectric thin-film-based optical filter on top of the photodetector fabricated using IC-compatible postprocessing; and 3) glass die on top containing the microchannels fabricated using SU-8 techniques. The application is in low-cost quantitative measurement of the concentration of biomolecules in biological fluids. Its operation is based on optical absorption in the part of the visible spectrum that is defined by the specific biomolecule. Signals proportional to the intensity of the light transmitted through the biological fluid are available at the output in the form of bit streams, which allows simple computer interfacing. The quantitative measurement of the total protein in urine is successfully demonstrated. The photodiode responsivity is 224 mA/W with a full-width at half-maximum of 10 nm at λ = 600 nm. The optical system sensitivity is 1 kHz/W m−2 at λ = 670 nm.